Photodynamic Therapy and Antibacterial Activities of a Novel Synthesized Quaternary Zn-Cu-In-S/ZnS QDs- mTHPP Porphyrin Conjugate - Tsolekile N; Parani S; de Macedo EF; Lebepe TC; Maluleke R; Ncapayi V; Matoetoe MC; Songca SP; Conceição K; Tada DB; Oluwafemi OS (International Journal of Nanomedicine, 2022)
Ncediwe Tsolekile,1– 3 Sundararajan Parani,2,3 Erenilda Ferreira de Macedo,4 Thabang Calvin Lebepe,2,3 Rodney Maluleke,2,3 Vuyelwa Ncapayi,2,3 Mangaka Clara Matoetoe,1 Sandile Phinda Songca,5 Katia Conceição,6 Dayane Batista Tada,4 Oluwatobi Samuel Oluwafemi2,3 1Department of Chemistry, Cape Peninsula University of Technology, Cape Town, 2000, South Africa; 2Department of Chemical Sciences, University of Johannesburg, Johannesburg, 2028, South Africa; 3Centre for Nanomaterials Science Research, University of Johannesburg, Johannesburg, South Africa; 4Laboratory of Nanomaterials and Nanotoxicology, Institute of Science and Technology, Federal University of São Paulo, São Paulo, Brazil; 5Department of Chemistry, University of KwaZulu-Natal, Durban, 4000, South Africa; 6Laboratory of Peptide Biochemistry, Institute of Science and Technology, Federal University of São Paulo, São Paulo, BrazilCorrespondence: Oluwatobi Samuel Oluwafemi, Department of Chemical Sciences, University of Johannesburg, P. O. Box 17011, Doornfontein, Johannesburg, 2028, South Africa, Tel +27 011 559 9060, Email oluwafemi.oluwatobi@gmail.com Dayane Batista Tada, Laboratório de Nanomateriais e Nanotoxicologia, Universidade Federal de São Paulo, Talim, 330 - Vila Nair, São José dos Campos, São Paulo, 12231-280, Brazil, Email day.tada@gmail.comBackground: Photodynamic therapy (PDT) is a non-invasive treatment modality that destroys abnormally growing cells or microorganisms. Porphyrins are used as photosensitizers in PDT; however, their clinical application has been limited by their poor water solubility, resulting in aggregation and low quantum yields of reactive oxygen species (ROS).Methods: To overcome these limitations and improve PDT efficacy, we herein report the conjugation of ZnCuInS/ZnS (ZCIS/ZnS) quantum dots (QDs) to 5,10,15,20-tetrakis(3-hydroxyphenyl)porphyrin (mTHPP). The optimal conditions for QDs porphyrin conjugation formation were systematically evaluated.Discussion: This study further assessed the PDT efficacy and antibacterial potency of the synthesized ZCIS/ZnS-mTHPP conjugates. The PDT efficacy of the QDs, mTHPP, and conjugate was evaluated against the murine metastatic melanoma (B16 F10 Nex2) cell line. This was performed with and without LED irradiation.Results: The conjugate exhibited the highest reduction in cell viability following LED irradiation (72%) compared to the bare QDs (19%) and mTHPP (1%). Antimicrobial studies conducted on E. coli showed that the conjugation exhibits a higher antibacterial effect than the bare QDs, even without light.Conclusion: The results suggest that conjugate is a promising class of materials for anti-cancer and antimicrobial PDT.Keywords: Zn-Cu-In-S/ZnS QDs, 5,10,15,20-tetrakis(hydroxyphenyl)porphyrin, mTHPP, photodynamic therapy, murine metastatic melanoma (B16F10-Nex2), antibacterial activity